Reflections of the Cult of Khidr-Elijah and the Hidrellez Tradition in the Alevi-Bektashi Community ın Bulgaria - Gramatikova, Nevana (Journal of Alevism-Bektashism Studies, 2022)
Hidrellez is a traditional holiday that has been very popular and actively celebrated all over the Turkic World for centuries. According to legend, this is the day on which the prophets Al-Khidr (Hizir) and Elijah (Ilyas) met, and the name of the holiday is a compound of their names. This holiday, also called Ruz-i Hizir, is the symbol of the nature’s revival, its new life and the continuous transition of the universe from death to life. Therefore, Hidrellez is celebrated in green areas, places where there are trees and water, and often in places associated with a tomb or a respected saint. It is believed that Khidr brings prosperity and fruitfulness to the place where he set his foot a night before Hidrellez. The Hidrellez tradition is one of the most respected and famous traditional holidays actively celebrated by the Alevi-Bektashi community in Bulgaria. It is both a manifestation of the cult of Khidr and a representation of the ancient Turkish holiday calendar and the practices of traditional rituals. Our paper focuses on some specific aspects of the cult of Khidr among the representatives of this community in Bulgaria, in a historical context. At the same time, it mentions some traditions and rituals performed during Hidrellez in the villages inhabited by Alevi-Bektashis in the Razgrad region (Bisertsi, Midrevo and Sevar), touches upon the symbolic elements of the games: Alaylar, Beşikli, Bezirgan, and analyses practices, such as Nişan çıkarma. The paper will also address the fact that these practices are carried out in parallel with the Hidrellez traditions of Alevi-Bektashis living in Turkey. An important point of this study is drawing attention to the revival of the traditional Hidrellez ritual system in Bulgaria for the last 10-15 years, expanding of its geographical scope, and as a result, gaining new features. The paper emphasis the role of the Hidrellez tradition in the revival and preservation of the Alevi-Bektashi identity in the period since 1990, after the democratic changes in the country. In Bulgaria, women, in particular, take part in the Hidrellez rituals. This fact shows and symbolizes the role and place of women within the Alevi-Bektashi community. Despite the changes of time and the pressure of modernization, women preserve the Hidrellez tradition with vigor. At the same time, Hidrellez rituals show how strong is the Turks’ respect for water, nature, trees, plants, fire and soil. We also witness this in the case of Bulgaria. This situation explains the universal dimensions of the holiday in question.